Ventriculosubgaleal shunting for spontaneous intraventricular haemorrhage: is it a good alternative to external ventricular drainage? - Amr Abu Elfadle; Carmen Ali Zarad; Ahmed Y. Soliman; Abdelmoneim Ahmed Nagy Eissa; Mohamed A. Elzoghby (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2022)
Abstract Background Spontaneous intraventricular haemorrhage (IVH) is a life-threatening condition associated with high morbidity and mortality and is conventionally managed using external ventricular drain (EVD). However, EVD is commonly associated with a high rate of complications, which necessitates another alternative management with a comparable or better outcome. This study aims to compare the efficacy and safety of ventriculosubgaleal shunt (VSGS) compared to EVD for the management of adult patients with spontaneous IVH. Results A total of 48 patients were enrolled in this study. Twenty patients underwent EVD and 28 had VSGS. Postoperative complications were non-significantly more prevalent in the EVD than in the VSGS group (75 vs. 64.3%, p = 0.430), including non-CR (20 vs. 32.1%), infection (20 vs. 7.1%), blocked ventricular catheter (15 vs. 3.6%), and dislodged catheter (10 vs. 7.1%). Convulsions and CSF leaks occurred more frequently in the VSGS group (7.1 vs 5%, p = 1.000). Postoperative GCS and Graeb’s score were comparable between the groups (p > 0.05). The EVD group had a non-significantly higher rate of hydrocephalus after ventricular catheter removal (80 vs. 53.6%, p = 0.059) and a higher mean GOS 3 months postoperatively (mean score: 4 vs. 3). Conclusions VSGS is as effective and safe compared to EVD, with a lower rate of infection, blocked/dislodged catheters, as well as a reduced incidence of hydrocephalus. On the other hand, EVD showed better GOS at 3 months. However, these differences did not reach statistical significance.